Pregnancy-Related Attack in Neuromyelitis Optica Spectrum Disorder With AQP4-IgG: A Single-Center Study and Meta-Analysis - Deng, Shuwen; Lei, Qiang; Lu, Wei (Frontiers in Immunology, 2022)
Abstract Objective: This study aimed to investigate the demographic characteristic of pregnancy-related attacks (PRAs) in neuromyelitis optica spectrum disorder (NMOSD). In addition, we investigated the predictors of PRAs as well as the effect of immunosuppressive (IS) therapy in patients with pregnancy-related NMOSD. Method: We retrospectively analyzed data on clinical and diagnostic characteristics, therapeutic management, and pregnancy outcomes for PRAs in AQP4-IgG-positive NMOSD patients admitted to the Second Xiangya Hospital of Central South University. Moreover, we searched the literature (without any temporal restriction) to identify all such similar cohorts and performed a meta-analysis to evaluate the effectiveness and safety of IS therapy on NMOSD patients with PRAs. Result: We collected clinical data on 117 women with AQP4 antibody-positive NMOSD; we ultimately included 33 patients (34 pregnancies). Ten patients were relapse-free during pregnancy, and 23 (69.7%) had PRA; attacks were most common during the first trimester of the postpartum period. Maintenance of IS treatment during pregnancy was found to greatly reduce PRAs in patients with NMOSD. PRAs were associated with a higher neutrophil-to-lymphocyte ratio (NLR) at relapse during pregnancy and shorter time interval between the last relapse and conception. The meta-analysis suggested that maintenance of IS treatment during pregnancy can significantly reduce the RR of NMOSD (95%CI=0.35=0.62; z=5.18, p<0.0001) and had no adverse effect on the miscarriage rate. However, the unhealthy newborn occurrence among those receiving IS treatment was 3.73 times higher than that of those not receiving treatment during pregnancy (95%CI=1.40–9.91; z=2.64, p=0.008). Conclusion: Our study results demonstrates that pregnancy can induce the onset or relapse of attacks in NMOSD patients. The increased NLR value and disease activity may be a predictor for PRAs in patients with NMOSD. Moreover, administration of IS treatment during pregnancy can reduce the relapse rate. However, the dosage of drugs and risks of adverse effects to the fetus need to be considered. Future prospective studies with larger sample sizes are needed to confirm and extend our findings.